PELAKSANAAN PEMBELAJARAN OLAHRAGA RENANG BAGI SISWA DISABILITAS INTELEKTUAL RINGAN (STUDI DESKRIPTIF DI SLB AISYIYAH SIJUNJUNG) - Ika Dewi Indriawati; Johandri Taufan; Damri Damri; Gaby Arneez; Syari Yuliana (STKIP Pesisir Selatan, 2025)
This study aims to describe the implementation of adaptive swimming instruction for students with mild intellectual disabilities at SLB Aisyiyah Sijunjung, focusing on the planning, implementation, and evaluation conducted by teachers, as well as the school’s support in meeting students’ learning needs. The study is motivated by the importance of adaptive physical education for students with special needs and the limited empirical research on swimming instruction in regional special schools. A qualitative descriptive approach was used. Data were collected through semi-structured interviews, participatory observations at the swimming pool, and document analysis of training programs, evaluation notes, and supporting archives. Data were analyzed using the Miles and Huberman model—data reduction, data display, and conclusion drawing—with credibility ensured through triangulation of sources, techniques, and time. The findings show that teachers design instructional plans gradually based on students’ individual needs and apply adaptive strategies such as demonstrations, repetition, task analysis, prompting, and positive reinforcement. The teaching process is structured from opening to closing activities, with adjustments aligned to students’ motor and cognitive abilities. Evaluation is carried out continuously through baseline assessment, ongoing assessment, and outcome evaluation based on individual progress rather than competitive standards.